Phenotype and Natural History of Children With Coexistent Inflammatory Bowel Disease and Celiac Disease. Issue 12 (16th January 2021) - Bramuzzo, Matteo; Lionetti, Paolo; Miele, Erasmo; Romano, Claudio; Arrigo, Serena; Cardile, Sabrina; Di Nardo, Giovanni; Illiceto, Maria Teresa; Pastore, Maria; Felici, Enrico; Fuoti, Maurizio; Banzato, Claudia; et al.
Abstract: Background: Adult patients with both inflammatory bowel disease (IBD) and celiac disease (CeD) have peculiar phenotypic features. This study aimed at describing the characteristics and natural history of children with both IBD and CeD. Methods: This was a case-control study based on a national registry. Cases included children diagnosed with both IBD and CeD. Two matched IBD controls without CeD, and 2 matched CeD controls were selected for each case. Inflammatory bowel disease phenotype and natural history, comprising growth and pubertal development, were compared between groups. Results: Forty-nine (1.75%) patients with IBD and CeD were identified out of 2800 patients with IBD. Compared with patients with IBD alone, patients with IBD and CeD presented more frequently with autoimmune diseases (odds ratio, 2.81; 95% CI, 0.97–8.37; P = 0.04). Ileocolonic localization (46.1% vs 73.1%), treatment with azathioprine (46.2% vs 71.2%), and anti-TNF biologics (46.2% vs 69.2%) were less common in patients with Crohn's disease and CeD than in patients with Crohn's disease alone. Patients with ulcerative colitis and CeD had an increased risk of colectomy despite similar medical treatments compared with patients with ulcerative colitis alone (13.0% vs 0%). Pubertal delay was more common in patients with IBD and CeD compared with patients with IBD alone (14.9% vs 3.2%; odds artio, 5.24; 95% CI, 1.13–33.0; P = 0.02) and CeD alone (14.9% vs 1.1%; P = 0.002). Conclusions: Children with IBD and CeD may have peculiar features with a higher risk for autoimmune diseases, colectomy, and pubertal delay compared with IBD alone.